2021
DOI: 10.1093/pm/pnaa432
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous Peripheral Nerve Stimulation of the Medial Branch Nerves for the Treatment of Chronic Axial Back Pain in Patients After Radiofrequency Ablation

Abstract: Objective Lumbar radiofrequency ablation is a commonly used intervention for chronic back pain. However, the pain typically returns, and though retreatment may be successful, the procedure involves destruction of the medial branch nerves, which denervates the multifidus. Repeated procedures typically have diminishing returns, which can lead to opioid use, surgery, or implantation of permanent neuromodulation systems. The objective of this report is to demonstrate the potential use of percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…Percutaneous PNS of the LMBN is a relatively new modality, and to date, there are 10 human, clinical studies focusing on nonspinal neuromodulation for chronic axial LBP (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Kapural et al (25) was the first to publish clinical data using the SPRINT device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous PNS of the LMBN is a relatively new modality, and to date, there are 10 human, clinical studies focusing on nonspinal neuromodulation for chronic axial LBP (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Kapural et al (25) was the first to publish clinical data using the SPRINT device.…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency pulse train stimulation of the LMBN terminal branches activates both sensory afferents and muscle efferent fibers, producing proprioceptive signals in large diameter fibers that convergently directly activate sensory afferents engaging in the spinal cord gating mechanism. Data are limited but have demonstrated sustained results, even after cessation of 60-day temporary stimulation for patients with multifactorial chronic axial low back pain, including degenerative disc disease, lumbar spondylosis, lumbar facet arthropathy, discogneic pain, etc (17,(20)(21)(22)(23)25). The permanently implanted restorative LMBN PNS system, on the other hand, has a more regimented minimally invasive technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to comment that long-term follow-up at 12 months demonstrated that 67% of enrolled subjects endorsed a 63% reduction in low back pain intensity after a 30-day trial of the externalized wearable stimulator, irrespective of etiology of low back pain. Deer et al’s subsequent study using the same methodology was also excluded because the enrolled population was too small and because of the extent of industry involvement [ 140 ]. However, these findings are supported by several other reports of simulation of other nerves which are of interest even though they did not meet the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviation: PNS, peripheral nerve stimulation. a One superficial infection at a lead exit site was resolved with removal of lead 1 week prior to end of treatment and an oral antibiotic (first reported in Deer et al 44 ).…”
Section: Ac K Now L E Dge M E N T Smentioning
confidence: 99%